Student attendance monitoring dashboard using codeIgniter and bootstrap framework / Siti Seha Salleh - Salleh, Siti Seha (2020)
This research develops a Dashboard for Monitoring Student Attendance system using QR Code technology that can record the attendance of the students in universities. QR Code can produce specific encrypted data that can be used for simultaneous encryption to ease the authentication process. The current practice of documenting attendance at most universities is by using a manual procedure to record student attendance through a paper-based approach. This practice will lead to inefficient handling of documents in class. The aim is to develop an attendance system using QR Code Technology. The aim is to develop a hybrid student attendance system application which will combine both web-based and mobile-based application in one development. CodeIgniter is a web application based on PHP. The system provides information about student attendance and able to generate QR Code based on the details about class attendance The significance of this project is to develop an effective dashboard for monitoring student attendance to help lecturers and students in universities to solve the inconvenience of taking attendance problems by using QR Code technology. The results show that all of the items asked were rated high above the average based on the usability test and user acceptance test conducted. Most of the respondents believe that this system is very helpful for lecturers and students to manage their attendance. Keywords: Monitoring Student Attendance, QR Code, Web Application and CodeIgniter